ARGUMENTS ON THE HISTORY OF IRRIGATION OF ANDIJAN (Scientific journal of the Fergana State University, 2023)
In this article different kind of theories are analysed about geographical place of Andijan city, historical position  of nine brooks  mentioned in “Boburnoma” by Z.M. Bobur and their contemporary conditions, related to  Andijansoy, saving and keeping its water clean.